STRATEGI PEMASAR ISLAMI DALAM MENINGKATKAN EKONOMI PEDAGANG DI PASAR BARU PAITON PROBOLINGGO - Ramdaniah, Fatih (An-Nisbah: Jurnal Ekonomi Syariah, 2019)
The development and competition of the business world in the current era of globalization is getting higher. This study aims to determine the marketing strategies of basic food traders in the new market of Paiton. The method used is qualitative based on observation, interviews, and documentation. The results of the study showed that the marketing strategies carried out by nine basic necessities traders used several strategies, among others, (a) service strategies, not easily discouraged when experiencing losses or being lazy when they made large profits; (b) product strategy, the accuracy of the opening time and checking the speed of serving the buyer can affect the reduction in income; (c) price strategy, price openness is needed in trading, so that the product (bargaining) process can be mutually beneficial; (d) promotion strategies, where traders approach emotionally to foster consumer trust, while fostering a high social life. Nevertheless, there are some deviations in marketing practices, such as the presence of elements of gharar or obscurity, the element of coercion and selling merchandise below market prices.